Correction: El-Sawah et al. Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Enhance Soil Key Enzymes, Plant Growth, Seed Yield, and Qualitative Attributes of Guar. Agriculture 2021, 11, 194 - Ahmed M. El-Sawah (MDPI AG, 2021)
In the original article [...]